Paranormal activity 2 [videorecording (DVD)] - Williams, Tod, 1968-; Featherston, Katie; Sloat, Micah (Paramount Home Entertainment, 2011)
Security cameras capture the torment as a demonic presence terrorizes new parents Dan and Kristi, tearing apart their seemingly perfect world and turning it into an inescapable nightmare.